2019
DOI: 10.1080/13548506.2019.1668567
|View full text |Cite
|
Sign up to set email alerts
|

The influence of personality on trajectories of distress, health and functioning in mild-to-moderately depressed adults with type 2 diabetes

Abstract: Identification of mental health risk is important for optimising diabetes care in type 2 diabetes mellitus (T2DM). Personality is linked to diabetes health and may assist detection of individuals with T2DM most at risk of chronic mental health difficulties. This study examined the moderator effect of personality factors on changes in psychological distress and functioning in adults with T2DM and mild-to-moderate depressive symptoms across a 12month period. Data were obtained from participants in a randomised c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(26 citation statements)
references
References 32 publications
2
24
0
Order By: Relevance
“…First, the results of the current study revealed that diabetes distress mediated the relationship between neuroticism and FoH. In this model, neuroticism was related to a high risk of diabetes distress and diabetes distress was associated with high risks of FoH, which was in line with previous studies ( Sanatkar et al, 2020 ; Li et al, 2021 ). Patients with diabetes need to adhere to hypoglycemic treatments and a series of management methods, such as diet control, for a long time due to the chronic and long-term nature of diabetes, which can easily give rise to negative emotions in patients ( Skinner et al, 2020 ).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…First, the results of the current study revealed that diabetes distress mediated the relationship between neuroticism and FoH. In this model, neuroticism was related to a high risk of diabetes distress and diabetes distress was associated with high risks of FoH, which was in line with previous studies ( Sanatkar et al, 2020 ; Li et al, 2021 ). Patients with diabetes need to adhere to hypoglycemic treatments and a series of management methods, such as diet control, for a long time due to the chronic and long-term nature of diabetes, which can easily give rise to negative emotions in patients ( Skinner et al, 2020 ).…”
Section: Discussionsupporting
confidence: 92%
“…More specifically, the more severe the diabetic distress of the patients, the stronger the FoH. Furthermore, a longitudinal study found that low neuroticism was linked with reduced diabetes distress over the course of a year ( Sanatkar et al, 2020 ), which suggests that diabetes distress may be a specific result of neuroticism. As a result, diabetes distress may be a mediating variable in the relationship between neuroticism and FoH.…”
Section: Introductionmentioning
confidence: 99%
“…Conscientiousness predicts Social Distancing and Wearing Masks and Gloves. This finding is congruent to a large body of research showing that conscientious individuals pay more attention to their health (e.g., Bogg & Roberts, 2013 ) and use more adaptive behaviour in health-related programs ( Sanatkar et al, 2020 ). In addition to these explanations, we found that conscientious individuals are more disciplined in wearing masks and gloves and keeping a distance from others due to their tendency to pursue attaining long-term goals (Getting as mediator), which is also consistent with previous studies (e.g., Murray, 2005 ).…”
Section: Discussionsupporting
confidence: 82%
“…In this sense, in times of self-isolation, conscientious people might have a greater tolerance for frustration and imposition relative to less conscientious people, who might engage in more impulsive behavior [ 96 ]. Moreover, previous research has indicated that conscientiousness may influence adaptive behavior, especially in health-related programs [ 99 , 100 ].…”
Section: Discussionmentioning
confidence: 99%